BOARD CHARACTERISTICS AND CORPORATE SOCIAL RESPONSIBILITY OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Ibrahim Halidu Saidu; Saidu Amina Umar (Gusau Journal of Accounting and Finance, 2024)
Understanding how board characteristics influence corporate social responsibility (CSR) remains a pressing concern for governance and sustainability in the banking sector. This study examined the impact of board characteristics measured by board size, board independence, and gender diversity on the CSR of listed deposit money banks in Nigeria. The research adopted a correlational research design and utilized secondary panel data spanning 2014 to 2023, with a population of 10 listed banks and a census sample of all. Data were sourced from publicly available annual reports and regulatory filings and analysed using simple multiple regression within a panel data framework. Findings reveal that board size, board independence, and gender diversity each have a statistically significant and positive influence on CSR expenditures. The study concludes that effective board composition especially larger, more independent, and gender-diverse boards enhances CSR engagement in the Nigerian banking context. It recommends that banks strengthen governance by expanding board size, ensuring a minimum 60% representation of independent directors, and increasing female participation to at least 30% in order to foster more ethical and socially responsible corporate behaviour.